Stimulation of bronchus-associated lymphoid tissue against Pasteurella multocida B:2 - Abd Wahid, Mohd Effendy; Ooi, Keng Wooi; Saad, Mohd Zamri (2007)
Forty clinically healthy goats at the age of approximately 7 months were equally divided into four groups. Those in Group 1, 2 and 3 were intranasally exposed to 1 mg, 1.5 mg and 2 mg of lyophilize crude containing 1.0x106 cfu/mL of P. multocida B2, respectively. The procedure was then repeated two weeks after the first inoculation. Group 4 remained as the untreated control group. ELISA was used to determine the levels of IgA and IgG in the serum and lung lavage fluids, while the right apical lobes lungs were cut into seven sections and examined for the sizes of bronchus-associated lymphoid tissues (BALT) and numbers of lymphocytes. Results showed that the levels of serum IgA and IgG were significantly higher (p<0.01) at 1.5 mg and 2 mg doses. Concurrently, the levels of IgA and IgG of the lung lavages were significantly higher (p<0.05) in all treated groups. The sizes of BALT and numbers of lymphocytes were significantly higher (p<0.05) after the first and second inoculation of 2 mg of the crude.